KEPERCAYAAN DAN PERILAKU K3 TERKAIT PENYAKIT DEKOMPRESI PADA PENYELAM ETNIS BAJO - Mallapiang, Fatmawaty; Syarfaini; Aeni, Syahtul; Jusriani, Rini; Azriful (Jurnal Kesehatan, 2024)
The total area of ​​Indonesian waters exceeds the land area, so that the sea becomes one of the land community livelihood. Majority of the Bajo ethnic community work as a traditional diver fisherman. This study aims to examine OSH beliefs and behaviors related to decompression sickness in Ethnic Bajo Divers. This type of research is qualitative using ethnographic study approach. Key informants in this study are ethnic Bajo divers who experience and who do not have paralysis. Data collection is done through, observation, in-depth interviews, and documentation, as well as triangulation of sources, methods and time. The beliefs and traditions of ethnic Bajo divers are related safety as well as prevention Decompression is before diving ask for safety to the Almighty Creator by saying greetings and basmalah and praying before diving which is a form of permission to The Guardian of the Sea. The Personal Protective Equipment that must be used were glasses (wooden/traditional glasses or glasses Ventara/modern). Decompression is understood as a disease cold with symptoms of cramps in the lower limbs obtained the result of diving for a long time at a certain depth so that they find sea water that is yellow like oil and very cold. It was concluded that ethnic Bajo divers still hold on to beliefs and traditions in doing diving, although some divers have switched to Modern divers use compressors.